2018
DOI: 10.3389/fimmu.2018.02858
|View full text |Cite
|
Sign up to set email alerts
|

Polarization of Human Macrophages by Interleukin-4 Does Not Require ATP-Citrate Lyase

Abstract: Macrophages exposed to the Th2 cytokines interleukin (IL) IL-4 and IL-13 exhibit a distinct transcriptional response, commonly referred to as M2 polarization. Recently, IL-4-induced polarization of murine bone marrow-derived macrophages (BMDMs) has been linked to acetyl-CoA levels through the activity of the cytosolic acetyl-CoA-generating enzyme ATP-citrate lyase (ACLY). Here, we studied how ACLY regulated IL-4-stimulated gene expression in human monocyte-derived macrophages (MDMs). Although multiple ACLY inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 45 publications
1
30
0
Order By: Relevance
“…The difference between our observations and the ones of Lauterbach et al might be explained by the knockdown method (i.e., short-term siRNA vs long-term LysMCre-driven) and other experimental variables. Clearly, the role of Acly in macrophages is stimulus-and time-dependent and also appears to depend on the experimental setting as Namgaladze et al observed no effect of Acly silencing 44 . As such, this is an area that warrants future research.…”
Section: Discussionmentioning
confidence: 99%
“…The difference between our observations and the ones of Lauterbach et al might be explained by the knockdown method (i.e., short-term siRNA vs long-term LysMCre-driven) and other experimental variables. Clearly, the role of Acly in macrophages is stimulus-and time-dependent and also appears to depend on the experimental setting as Namgaladze et al observed no effect of Acly silencing 44 . As such, this is an area that warrants future research.…”
Section: Discussionmentioning
confidence: 99%
“…In M2 macrophages ACLY is regulated by the Akt-mTORC1 axis, leading to histone acetylation and induction of some M2 genes (87). However, a recent study has shown that polarization of human macrophages toward an M2 phenotype does not require ACLY (88).…”
Section: The Krebs Cyclementioning
confidence: 99%
“…Type 2 cytokines (e.g., IL-4) are involved in M2 macrophage polarization. Response to IL-4 may differ between mouse and human macrophages (19,20). This M1/M2 dichotomy is known to be associated with a distinct arginine metabolism, in particular for mouse macrophages (21,22).…”
Section: Arginine Metabolism a Well-described Pathway Differing Betwmentioning
confidence: 99%